YAP inactivation-mediated autophagy inhibition contributes to cisplatin resistance in ovarian cancer cells - Ngoc Thang Nguyen; Meng-Ru Hsieh; Hieu Dac Hanh Nguyen; Waratchaya Chimphlee; Sarinporn Visitsattapongse; Wen‐Tai Chiu (Journal of Ovarian Research, 2026)
BACKGROUND: Cisplatin resistance remains a critical barrier in the treatment of high-grade serous ovarian cancer (HGSOC). Although Hippo-YAP signaling regulates cancer progression, its contribution to cisplatin resistance is still poorly understood. Here, we demonstrate that YAP is inactivated and sequestered in the cytoplasm of cisplatin-resistant ovarian cancer cells. RESULTS: This cytosolic retention is mediated by Hippo kinases MST1/2 and LATS1/2, as well as ERK signaling, resulting in increased phosphorylation of YAP at its inhibitory site (Ser397) and reduced phosphorylation at its activating site (Tyr357). Restoration of YAP activity through genetic overexpression or pharmacological induction of nuclear YAP accumulation significantly reversed cisplatin resistance. Mechanistically, YAP inactivation impaired cisplatin-induced autophagy. Cisplatin robustly triggered autophagy in parental cells, as evidenced by LC3 puncta formation; however, this autophagic response was blunted in resistant cells. Overexpression of YAP further suppressed LC3 puncta formation and Beclin-1 expression, and increased p62 accumulation in cisplatin-resistant ovarian cancer cells. Autophagy inhibition using 3-methyladenine (3-MA) resensitized resistant cells to cisplatin. CONCLUSION: Collectively, these findings reveal that YAP inactivation contributes to cisplatin resistance by abrogating autophagy formation and identify YAP reactivation as a potential strategy to overcome chemoresistance in ovarian cancer.
Keywords: Hippo pathway signaling and YAP/TAZ; Autophagy in Disease and Therapy; Cancer Mechanisms and Therapy